Horizon scanning to assess the bioclimatic potential for the alien species Spodoptera eridania and its parasitoids after pest detection in west and central Africa - Tepa-Yotto, Ghislain T.; Gouwakinnou, G.N.; Fagbohoun, J.R.; Tamo, Manuele; Saethre, M. (Wiley, 2021)
BACKGROUND The southern armyworm (SAW) Spodoptera eridania (Stoll) (Lepidoptera: Noctuidae) is native to the tropical Americas where the pest can feed on more than 100 plant species. SAW was recently detected in West and Central Africa, feeding on various crops including cassava, cotton, amaranth and tomato. The current work was carried out to predict the potential spatial distribution of SAW and four of its co-evolved parasitoids at a global scale using the maximum entropy (Maxent) algorithm.